2020
DOI: 10.1186/s43168-020-00030-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel coronavirus disease 2019 (COVID-19) non-respiratory involvement

Abstract: Background Coronavirus disease 2019 (COVID-19) is a newly emerging pandemic that affected millions of people worldwide caused by novel coronavirus SARS-CoV-2. The first cases reported suffered from respiratory symptoms. Main body Various extrapulmonary manifestations were linked to COVID-19 in several reports including cardiovascular, genitourinary, gastrointestinal, and skin. It is important that every clinician should be aware of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Additionally, most keywords were related to respiratory issues, which were the most common symptoms during the early waves of COVID-19 [ 32 ]. More recent studies have reported nonrespiratory symptoms of COVID-19 [ 33 - 36 ] that we incorporated, but we were unable to use a more accurate method, such as COVID-19 test results to evaluate how the recurring pandemic waves relate to telemedicine use. Additionally, satisfaction data were only available for VUC visits.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, most keywords were related to respiratory issues, which were the most common symptoms during the early waves of COVID-19 [ 32 ]. More recent studies have reported nonrespiratory symptoms of COVID-19 [ 33 - 36 ] that we incorporated, but we were unable to use a more accurate method, such as COVID-19 test results to evaluate how the recurring pandemic waves relate to telemedicine use. Additionally, satisfaction data were only available for VUC visits.…”
Section: Discussionmentioning
confidence: 99%
“…9 Poor outcomes in COVID-19 were linked to severe respiratory involvement, cardiac, and renal involvement. 10 Previous reports showed that comorbidities like COPD, and diabetes mellitus were linked to poor outcomes. 11 Significant independent potential predictors of in-hospital mortality were reported in elderly COVID-19 patients including hypernatremia [HR 9.1], lymphopenia [HR7.4], and cardiovascular disease (CVD) other than hypertension [HR6.4].…”
Section: Introductionmentioning
confidence: 99%